Sterically Stabilized RIPL Peptide-Conjugated Nanostructured Lipid Carriers: Characterization, Cellular Uptake, Cytotoxicity, and Biodistribution - Chang Hyun Kim; Si Woo Sung; Eun Seok Lee; Tae Hoon Kang; Ho Yub Yoon; Yoon Tae Goo; Ha Ra Cho; Dong Yoon Kim; Myung Joo Kang; Yong Seok Choi; Sangkil Lee; Young Wook Choi (MDPI AG, 2018)
As a platform for hepsin-specific drug delivery, we previously prepared IPLVVPLRRRRRRRRC peptide (RIPL)-conjugated nanostructured lipid carriers (RIPL-NLCs) composed of Labrafil® M 1944 CS (liquid oil) and Precirol® ATO 5 (solid lipid). In this study, to prevent the recognition by the mononuclear phagocyte system, polyethylene glycol (PEG)-modified RIPL-NLCs (PEG-RIPL-NLCs) were prepared using PEG3000 at different grafting ratios (1, 5, and 10 mole %). All prepared NLCs showed a homogeneous dispersion (130⁻280 nm), with zeta potentials varying from −18 to 10 mV. Docetaxel (DTX) was successfully encapsulated in NLCs: encapsulation efficiency (93⁻95%); drug-loading capacity (102⁻109 µg/mg). PEG-RIPL-NLCs with a grafting ratio of 5% PEG or higher showed significantly reduced protein adsorption and macrophage phagocytosis. The uptake of PEG(5%)-RIPL-NLCs by cancer cell lines was somewhat lower than that of RIPL-NLCs because of the PEG-induced steric hindrance; however, the uptake level of PEG-RIPL-NLCs was still greater than that of plain NLCs. In vivo biodistribution was evaluated after tail vein injection of NLCs to normal mice. Compared to RIPL-NLCs, PEG(5%)-RIPL-NLCs showed lower accumulation in the liver, spleen, and lung. In conclusion, we found that PEG(5%)-RIPL-NLCs could be a promising nanocarrier for selective drug targeting with a high payload of poorly water-soluble drugs.